A polymer–metal–polymer–metal heterostructure for enhanced photocatalytic hydrogen production. Issue 1 (20th November 2014) - Zhang, Yifeng; Mao, Fang; Yan, Hongjian; Liu, Kewei; Cao, Hongmei; Wu, Jiagang; Xiao, Dingquan
Abstract : The tightly coupled heterostructure g-C3 N4 /Au/poly(3-hexylthiophene) (P3HT)/Pt was successfully prepared by a self-assembling method. Abstract : The tightly coupled heterostructure g-C3 N4 /Au/poly(3-hexylthiophene) (P3HT)/Pt was successfully prepared by a self-assembling method. The heterojunction photocatalyst displayed high activity for hydrogen production from water which contains triethanolamine as an electron donor under visible light irradiation. The samples were characterized by X-ray diffraction (XRD), UV-visible spectroscopy, photoluminescence (PL) spectra analysis and transmission electron microscopy (TEM). The experimental results demonstrated that the g-C3 N4 /Au/P3HT/Pt structure was conducive to the efficient separation of photo-generated electron–hole pairs, which can be explained by the strong junction of chemical bond between Au and P3HT. The effect of P3HT content on the activity of the photocatalysts was investigated with a series of g-C3 N4 /Au/P3HT heterostructure samples loaded with Pt as a cocatalyst in triethanolamine aqueous solutions. The optimal P3HT content was determined to be 0.5 wt%, and the corresponding hydrogen evolution rate was 320 μmol h −1 .